Influenza virus subtype/lineage-specific seasonal patterns and age-related infection risk, in Eastern China - Xiang Huo; Junjie Fu; Qigang Dai; Fengcai Zhu (Journal of Infection in Developing Countries)
Introduction: Differences in seasonal pattern and age-related infection risk have been reported between Influenza type A and B, but have not been elaborated at subtype/lineage level.